A Sociopsychological Analysis of the Profiles of the Earliest Muslims and the Nature of the Islamic Call - Mücahit Yüksel; Hakan Temir (İslami İlimler Dergisi)
Islam is the religion preached by all prophets, from the first human being and the first prophet, Adam, to the last prophet, Muhammad. However, over time, people have deviated from it due to various psychological, sociological, cultural, and economic reasons and have adopted false religions. Thus, an overwhelming number of people are on multiple paths other than what is revealed to the Prophets. At this point, one may ask, “Why do people deviate from the path of Islam and follow others?” In this article, we will attempt to understand the issue at its core by focusing on the beginning of the end. By “the end,” we mean that the divine will, which seeks to eradicate falsehoods, selects a new messenger to warn people about the corruption of previous beliefs and calls them to embrace a new religious formation. At this point, when humanity is faced with choices of right and wrong, it is important to examine both states of mind. This can be done by studying the invitation of the last Prophet Muhammad, the characteristics of the first Muslims who responded to it, and why some rejected the invitation. However, it is crucial to approach this issue transparently and realistically; otherwise, the true essence of the matter will be lost. Various statements have been made by different groups, particularly orientalists, about the attributes of the early Muslims and their motivations for embracing the Islamic call. It is important to clarify these arguments to uncover the truth behind them. Some have suggested that the first Muslims were generally weak and young. Thus, they propose reasons such as “the desire to end victimization” and “lack of rational thinking due to youth” as justifications for accepting the call. Consequently, the divine origin, message content, conformity to human nature, and organizing principles of the Islamic call are overlooked. Therefore, the aim of this article is to consolidate and analyze both claims and facts and draw conclusions about the true nature of the issue without getting caught up in unnecessary debates.